Ultrasound‐guided fine‐needle aspiration cytology significantly improved mycetoma diagnosis. (6th July 2022) - Siddig, E.E.; El Had Bakhait, O.; El nour Hussein Bahar, M.; Siddig Ahmed, E.; Bakhiet, S.M.; Motasim Ali, M.; Babekir Abdallah, O.; Ahmed Hassan, R.; Verbon, A.; van de Sande, W.W.J.; Fahal, A.H.
Abstract: Background: Ultrasound (US)‐guided fine‐needle aspiration cytology (US‐FNAC) has improved the diagnosis of many malignancies, infections and other diseases as it is safe, simple, quick and accurate. In mycetoma, it is assumed that this technique may have a better diagnostic yield than the conventional FNAC as it can accurately identify the optimal site for the aspiration. Objective: To compare the diagnostic yield of conventional FNAC with US‐FNAC. Methods: This descriptive cross‐sectional hospital‐based study included 80 patients with clinically suspected mycetoma. Results: Of the 80 patients included, 35 proved to have actinomycetoma, and 37 had eumycetoma based on surgical biopsies, histopathological examination and the culture of grains. Eight patients appeared to have no mycetoma. For actinomycetoma diagnosis, the US‐guided FNAC improved sensitivity to 97% and negative predictive value (NPV) to 83% compared to the conventional FNAC, which had 63% sensitivity; and NPV of 28%. No improvement was found for specificity. For eumycetoma, the conventional FNAC had 86.5% sensitivity, 100% specificity, 100% PPV and 37.5% NPV. The US‐FNAC for the diagnosis of eumycetoma had 100% sensitivity and specificity. Conclusions and relevance: The obtained results showed that US‐FNAC is better than the conventional FNAC with lower false‐negative results. It can accurately distinguish between the two types of mycetoma, allowing rapid initiation of proper treatment. The technique can be used in rural areas with low resources and for epidemiological surveys as a quick screening tool for patients suspected of mycetoma.